Challenges and limitations to HIV testing and counselling (HTC) in a Sub-Saharan HIV low prevalence country : the case of Burkina Faso - (:unkn) unknown (My University, 2016)
Background. Treatments are effective for people living with HIVAIDS (PLWHA) care and prevention. However, only 55% of PLWHA are aware of their status. This rate is lower in Central and West Africa (35%). In July 2015, WHO published new guidelines on HIV testing. In Sub-Saharan Africa, there are many studies which results are used to define policies and guidelines on HIV testing at the international level. Few of them are implemented in low HIV prevalence countries, notably French-Speaking West Africa. The overall objective of this thesis is to analyze the challenges and limitations of HIV testing and counselling (HTC) policies and programs in low prevalence countries, over the situation in Burkina Faso and propose new measures to increase the access to HTC services.Methods. Two studies have been conducted. The first one was carried out in the « Multi-country African Testing and Counselling for HIV » (MATCH) project which was implemented in four countries (Burkina Faso, Kenya, Malawi, Uganda). It aimed to analyze the motivations and barriers to HTC services practices by users, non-users and providers. In Burkina Faso, the study was carried out in Urban (Ouagadougou) and rural (Dédougou) areas in 2008-2009. In each locality, study sites (client initiated testing and provider initiated testing sites) were chosen, given the level of utilization. Quantitative and qualitative methods were used. The second study was conducted in 2015, with HTC providers and decision makers at national level. The objective was to analyze their perceptions on WHO 2015 guidelines. A data collection tool explaining the changes introduced in the guidelines has been designed and transmitted via electronic means. Their opinions were analyzed.Results. Guidelines for HTC in Burkina Faso were from 2008. In client initiated testing sites, there were more women (58.5%). However, men (p=0.02), 18-34 years old (p=0.01), and the more educated ones (p=0.001) appeared to have used early se
Keywords: African Research